Social ecology in the digital age : solving complex problems in a globalized world - Stokols, Daniel (Academic Press, an imprint of Elsevier, 2018)
Social Ecology in the Digital Age: Solving Complex Problems in a Globalized World provides a comprehensive overview of social ecological theory, research, and practice. Written by renowned expert Daniel Stokols, the book distills key principles from diverse strands of ecological science, offering a robust framework for transdisciplinary research and societal problem-solving. The existential challenges of the 21st Century - global climate change and climate-change denial, environmental pollution, biodiversity loss, food insecurity, disease pandemics, inter-ethnic violence and the threat of nuclear war, cybercrime, the Digital Divide, and extreme poverty and income inequality confronting billions each day - cannot be understood and managed adequately from narrowiAdisciplinary or political perspectives. Social Ecology in the Digital Age is grounded in scientific research but written in a personal and informal style from the vantage point of a former student, current teacher and scholar who has contributed over four decades to the field of social ecology. The book will be of interest to scholars, students, educators, government leaders and community practitioners working in several fields including social and human ecology, psychology, sociology, anthropology, criminology, law, education, biology, medicine, public health, earth system and sustainability science, geography, environmental design, urban planning, informatics, public policy and global governance.